Differentiating between the diffusion of water and ions from aqueous electrolytes in organic coatings using an integrated spectro-electrochemical technique. (March 2023) - Madelat, Negin; Wouters, Benny; Jalilian, Ehsan; Van Assche, Guy; Hubin, Annick; Terryn, Herman; Hauffman, Tom
Abstract: In this work, the separate diffusion of water and ions through a polyethylene glycol diacrylate (PEGDA) coating was characterized using an integrated spectro-electrochemical technique. The ions ingress front position profile along the thickness of the coating was derived from fitting odd random phase electrochemical impedance spectroscopy (ORP-EIS) data using a physically relevant electrochemical equivalent circuit (EEC). The arrival time of the ions at the coating/metal oxide buried interface obtained from EEC and rapid uptake of water was verified using in situ attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR) measurements in Kretschmann geometry integrated in the ORP-EIS set-up. Highlights: The independent diffusion of ions through an organic coating was studied. An integrated spectro-electrochemical technique consisting of ORP-EIS combined with ATR-FTIR in Kretschmann geometry was utilized. ORP-EIS measurements were carried out in situ and in the same time frame as ATR-FTIR measurements. The ORP-EIS results were fitted using a physically appropriate equivalent circuit. The time of the arrival of the ions at the buried interface was extracted from the fitting results and was verified using ATR-FTIR measurements.